Implementasi Kurikulum Merdeka di SDN Kebonsari 1/414 Surabaya - Putri, Vinaya Andiny; Latifah, Dian Nur; Rosydiana, Maya; Firmansyah, M. Rafly; Amalia, Kaniati (Lembaga Yasin AlSys, 2024)
Curriculum anatomy is described as components that must exist in every educational institution. The curriculum is one of the educational tools or components that plays a very important role in delivering the expected educational goals. The aims of the curriculum itself are formulated based on the development of demands, needs and conditions of society and are based on thoughts and are directed at achieving philosophical values, especially state philosophy. This article aims to discuss the curriculum implemented at SDN Kebonsari 1/414 Surabaya. By using a qualitative descriptive approach method with observation data collection and literature review methods, the research results show that curriculum management involves planning, development, implementation and evaluation of school or college curricula. In this abstract, we will generally discuss topics such as curriculum implementation planning, curriculum implementation, the process of implementing the new curriculum in the school, the advantages and disadvantages of implementing the new curriculum, how the curriculum affects the school, what are the positive and negative impacts of the curriculum, and how to evaluate to increase its effectiveness.